2020
DOI: 10.1088/2515-7620/ab6368
|View full text |Cite
|
Sign up to set email alerts
|

Economy-wide effects of coastal flooding due to sea level rise: a multi-model simultaneous treatment of mitigation, adaptation, and residual impacts

Abstract: This article presents a multi-model assessment of the macroeconomic impacts of coastal flooding due to sea level rise and the respective economy-wide implications of adaptation measures for two greenhouse gas (GHG) concentration targets, namely the Representative Concentration Pathways (RCP)2.6 and RCP4.5, and subsequent temperature increases. We combine our analysis, focusing on the global level, as well as on individual G20 countries, with the corresponding stylized RCP mitigation efforts in order to underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Finally, progress can come from combining models of different types as well as their structured comparison, such as (88). For example, biophysical model outputs can be used as the independent variables for estimating micro-and macroeconomic econometric models, with the potential for both improving the predictability of these models and avoiding the parameterization of the biophysical relationship.…”
Section: Discussion and Suggestions For The Way Forwardmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, progress can come from combining models of different types as well as their structured comparison, such as (88). For example, biophysical model outputs can be used as the independent variables for estimating micro-and macroeconomic econometric models, with the potential for both improving the predictability of these models and avoiding the parameterization of the biophysical relationship.…”
Section: Discussion and Suggestions For The Way Forwardmentioning
confidence: 99%
“…Short-run adaptation to weather fluctuations should be distinguished from long-run adaption to climate change (15), adaptation can occur in various sectors under different forms, and the adaptation decision can occur at a small scale (86) or at the wider global scale, in particular, the research and development of adaptive technologies (6). Some studies found substantial impact reductions through adaptation to future climate (38,87,88), but empirical evidence for adaptation to ongoing climate is mixed (7,89,90).…”
Section: The Role Of Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…The human, environmental, and financial costs of inaction and failure to adapt to climate change are enormous. It is estimated that losses from flood damage due to a sea level rise of 1.3 m could equal 4% of global gross domestic product (currently US$4 trillion) annually (Ichinko et al 2019). At present, global infrastructure valued at US$100 trillion is at risk and underinsured.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the world's coastlines have limited data observation, in contrast to the coastal zone where the megacities are located [8]. Sea levels are rising due to global warming, and this trend is anticipated to continue and increase in the next decades [9], resulting in more frequent coastal flooding, material asset destruction, and an elevated risk of human death [10]. These effects will be accentuated by the great concentration of activities, services, and people in coastal cities.…”
Section: Introductionmentioning
confidence: 99%